2022
DOI: 10.1186/s12985-022-01894-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis of human papillomavirus 67 isolated from Japanese women with cervical lesions

Abstract: Background Human papillomavirus (HPV) type 67 is phylogenetically classified into Alphapapillomavirus species 9 (alpha-9) together with other carcinogenic types (HPV16, 31, 33, 35, 52 and 58), but is the only alpha-9 type defined as possibly carcinogenic. This study aimed to determine whole-genome sequences of HPV67 isolated from Japanese women with cervical cancer or cervical intraepithelial neoplasia (CIN) to better understand the genetic basis of the oncogenic potential of HPV67. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…HPV 67, a potential HR HPV was noted as the most prevalent among HIV-positive patients. In a study done among Japanese women with cervical lesions, the genome analysis of HPV 67 suggested the carcinogenic potential of this rare genotype (25). The high prevalence of HPV among HIV-positive patients indicates the need for further clinical and epidemiological follow-up study on the role of other HR and potential HR HPV in cervical diseases especially among immune-compromised population.…”
Section: Urban-jootrhmentioning
confidence: 99%
“…HPV 67, a potential HR HPV was noted as the most prevalent among HIV-positive patients. In a study done among Japanese women with cervical lesions, the genome analysis of HPV 67 suggested the carcinogenic potential of this rare genotype (25). The high prevalence of HPV among HIV-positive patients indicates the need for further clinical and epidemiological follow-up study on the role of other HR and potential HR HPV in cervical diseases especially among immune-compromised population.…”
Section: Urban-jootrhmentioning
confidence: 99%
“… 5 International agency for research on cancer institutions classify HPV16, 18, 31, 33, 39, 45, 51, 52, 56, 58, and 59 as carcinogens (group 1), HPV68 may cause cancer (group 2A), and HPV26, 53, 66, 67, 70, 73, and 82 are classified as being possibly carcinogenic (group 2B). 6 …”
Section: Introductionmentioning
confidence: 99%